If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = (x + 2) * 8 + 6 Reorder the terms: 6x = (2 + x) * 8 + 6 Reorder the terms for easier multiplication: 6x = 8(2 + x) + 6 6x = (2 * 8 + x * 8) + 6 6x = (16 + 8x) + 6 Reorder the terms: 6x = 16 + 6 + 8x Combine like terms: 16 + 6 = 22 6x = 22 + 8x Solving 6x = 22 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6x + -8x = 22 + 8x + -8x Combine like terms: 6x + -8x = -2x -2x = 22 + 8x + -8x Combine like terms: 8x + -8x = 0 -2x = 22 + 0 -2x = 22 Divide each side by '-2'. x = -11 Simplifying x = -11
| -11=-2+-1y | | (v/6)=13 | | 3y^2-12y+15=0 | | 4+9n=6n+4 | | (4a^2-7a+12)(a^2+2a-3)= | | 6+a=49 | | .5+.666p+6=4p-1-.8333p | | 3(-6-6x)=198 | | 1/4*9= | | -42=7k | | (x^4/9)^2 | | 3(3+6x)=129 | | 1.5=3 | | 5+7(8r-2)=0 | | .25x+5=.75x+2 | | y=19x+2500 | | 5m+31=9m-2 | | 9-1y=4 | | -5(3+6x)=-15 | | (x-1)+5=230 | | =48+25 | | 5c-2a=1 | | 15.(-2/3) | | 10=-2+n | | x^2-8x+23=f(x) | | 4a+3b=17 | | 5(2+1)=45 | | 2x^2a+2xa^2= | | 2(11+3n)=23 | | B+10=50 | | 8y-5=51 | | logx-3logy=4 |